Photographic stories on prevention of psychoactive substances on socially vulnerable schoolers (2019)
A research was conducted in the educational institution Las Brisas, located in the commune Villa Santana (Pereira, Colombia), motivated by three local teachers concerns for the future of the current generation of social vulnerability scenarios. Social mapping was used as context recognition technique. The aim was to describe how they got impacted by photographic stories in the prevention of psychoactive substances in children of that institution. The design was descriptive, with pretests, photography workshops and awareness resilience. The photograph moved deep down the feelings of the children expressed in different stories and allowed to outsource feelings of hope and fear, glimpsing elements in the process of drug prevention.